Synthesis of carbon nanotubes using different source of carbon - 298841 Noor Nadiah Oman (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Kimia Industri) - Universiti Teknologi Malaysia, 2006